Detection of the active compounds in the leaves of the Common mallow plant Malva parviflora L. using GC-MS and HPLC technology. - Kawthar Kadhim Al- Qarawi; Hamid Majid Rashid Al-Obaidi (Kufa Journal for Agricultural Sciences)
The plant leaves of Common mallow plant were collected from the gardens of college of Agriculture ,University of Kufa to detect the active compounds of this plant. The plant was dried in the shade at room temperature and grinding a log of plant leaves and used to detect the active compounds in the laboratories of the Ministry of Science and Technology using GC-MS and HPLC. The results ofanalysis showed that commonmallow leaves contained many of active compounds such as kaempherol, Rutin, QurcetineandLuteolin when analyzed by a HPLC. Either When analyzeedby GC-MS the result showed that it contained 9,12-Octadecadioenaic acid(z,z),methyl ester and 10,13-Octadecadioenaic acid, methyl ester at a percentage of 70.58% and Hexadeanoic acid, methyl esterat a percentage 8.42%.